Power Aware Energy Efficient Cluster Based Network Coding Algorithm for Dynamic Source Routing (PA-EECSNC DSR) - J. , Lakshmi; R. , Latha (International Journal of Psychosocial Rehabilitation, 2020)
A Wireless Sensor Network (WSN) is built by means of sensor motes that are in use to study the information about the environment, like daylight, high temperature, moisture, pressure, location, tremor, noise, etc. To carry out a variety of responsibilities like smart detecting, a detection of neighbor node, data processing and storage, data compilation, target tracking, monitoring and controlling, synchronization, node localization, and effective routing, these nodes can be used in different real-time applications between the base station and nodes. WSNs are great networks of small embedded devices, each with sensing, computation, and communication capabilities. Developments and execution of low-power microcontrollers based on wireless sensors have been improved fast to resolve a lot of real-life troubles like traffic monitoring, patient monitoring, and battlefield surveillance. Sensing, calculations, and communication are routines of wireless sensor networks that consume more power of these sensor nodes. Since sensor nodes have small batteries with a restricted life, power management is necessary to be addressed to make sensors work for a long time with an effective and efficient power management scheme. This research concentrates on introducing a new algorithm for cluster-based energy saving over the DSR protocol. The proposed work is implemented and evaluated in OMNet++.